Innovation, agile project management and firm performance in a public sector-dominated economy: empirical evidence from high-tech small and medium-sized enterprises in China - Ju, X.; Ferreira, F.; Wang, M. (Socio-Economic Planning Sciences, 2020)
While agile project management has become increasingly important for high-tech small and medium-sized enterprises (SMEs), firm performance varies greatly due to companies’ different degrees of innovation capability and internal and external environmental dynamics. Drawing on the resource-based view – as well as innovation capability and agile project management theories – a comparative analysis was conducted of two high-tech SMEs. The results were used to develop a theoretical model based on six hypotheses. Empirical research was carried out that included measurement of key variables, data collection and analysis, validity and reliability tests, regression analysis, and structural equation modeling, which confirmed five of the six initial hypotheses. The proposed model incorporates different innovation capability roles, considers project agility enhancement of firm performance, and takes into account interactions between companies’ innovation atmosphere and environmental dynamics in a public sector-dominated economy (i.e., China). The results contribute to project agility magement’s theoretical development and refinement by presenting new findings on innovation and environmental dynamics. The results also provide guidelines for project agility practices in high-tech SMEs in China, with the potential to improve these firms’ performance. Implications and limitations are also discussed.